The Role of Vulnerable and Grandiose Narcissism in Psychological Perpetrated Abuse Within Couple Relationships: The Mediating Role of Romantic Jealousy. Issue 2 (17th February 2020) - Ponti, Lucia; Ghinassi, Simon; Tani, Franca
Abstract: The aim of this study was to analyze the direct and indirect relationships between the two phenotypes of narcissism, vulnerable and grandiose, and the tendency to perpetrate psychological abuse, exploring the mediating role of romantic jealousy. Our sample included 473 participants (213 males), aged 18–30 years ( M = 22.74; SD = 2.81), involved in a stable romantic relationship. A structural equation modeling was conducted to test our model and a multigroup analysis was performed to test gender differences. Results show that the two forms of narcissism are both linked to psychological perpetrated abuse, but in different ways. Vulnerable narcissism was linked to psychological abuse only indirectly, through the role of romantic jealousy. On the contrary, grandiose narcissism was positively and directly associated with psychological abuse within the romantic relationship. Moreover, the model was invariant across genders. Limitations, strengths, and theoretical and clinical implications are discussed.